The role of attitude towards green in mediating the effect of environmental concern and green perceived value on green purchase intention: A study of Gen Z’s behavior toward Sensatia Botanicals in Denpasar City - Supartha, Anak Agung Ayu Rika Putri; Sukaatmadja, I Putu Gde (International research journal of management, IT and social sciences, 2025)
This study examines the mediating role of attitude towards green in the relationship between environmental concern, green perceived value, and green purchase intention. The research focuses on Generation Z’s behavior toward Sensatia Botanicals in Denpasar City, using the Theory of Planned Behavior (TPB) as the theoretical framework.The study adopts a quantitative, associative research design. The target population consists of Gen Z individuals in Denpasar who have never purchased Sensatia Botanicals’ eco-friendly cosmetic products. Using purposive sampling, 112 respondents were selected, and data were collected through questionnaires. Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) was employed for data analysis. Findings reveal that environmental concern, green perceived value, and attitude towards green positively and significantly influence green purchase intention. Moreover, attitude towards green partially mediates the effects of environmental concern and green perceived value on green purchase intention for Sensatia Botanicals. Theoretically, this research enriches the TPB by providing empirical insights into the relationships among key green behavioral variables. Practically, Sensatia Botanicals can strengthen its marketing strategy by creating educational campaigns emphasizing eco-friendly, functional, and emotional product benefits. Additionally, offering incentives can foster stronger emotional connections, enhance purchase intention, and build a sustainability-conscious community.